2019
DOI: 10.1016/j.ymthe.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 Inhibition in Ewing Sarcoma Upregulates GD2 Expression for Targeting with Gene-Modified T Cells

Abstract: Chimeric antigen receptor (CAR) engineering of T cells allows one to specifically target tumor cells via cell surface antigens. A candidate target in Ewing sarcoma is the ganglioside G D2 , but heterogeneic expression limits its value. Here we report that pharmacological inhibition of Enhancer of Zeste Homolog 2 (EZH2) at doses reducing H3K27 trimethylation, but not cell viability, selectively and reversibly induces G D2 surface expression in Ewing sarcoma cells. EZH2 in Ewing sarcoma cells directly binds to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 62 publications
1
88
0
1
Order By: Relevance
“…8 Recently, it was shown that EZH2 inhibition together with chimeric antigen receptor (CAR) T cell therapy is an interesting novel immunotherapeutic treatment approach in EWST, as it leads to upregulation of the immune target ganglioside G D2 . 38 Similar to adult tumor types, the relative contribution of total T cells correlates directly with a better OS and EFS (training cohort: p = .044, p = .032, respectively; validation cohort: p = .005, p = .02, respectively) in ESFT. Previously, it has been demonstrated that HLA-G, a non-classical, immuneinhibitory MHC class 1 molecule is expressed in tumor cells and/or lymphocytes in ESFT primary tumor samples.…”
Section: Discussionmentioning
confidence: 93%
“…8 Recently, it was shown that EZH2 inhibition together with chimeric antigen receptor (CAR) T cell therapy is an interesting novel immunotherapeutic treatment approach in EWST, as it leads to upregulation of the immune target ganglioside G D2 . 38 Similar to adult tumor types, the relative contribution of total T cells correlates directly with a better OS and EFS (training cohort: p = .044, p = .032, respectively; validation cohort: p = .005, p = .02, respectively) in ESFT. Previously, it has been demonstrated that HLA-G, a non-classical, immuneinhibitory MHC class 1 molecule is expressed in tumor cells and/or lymphocytes in ESFT primary tumor samples.…”
Section: Discussionmentioning
confidence: 93%
“…We first reassessed the well-established second generation CAR targeting the cell-surface ganglioside G D2 with respect to specific target recognition. The G D2 CAR contains a single-chain variable fragment (scFv) derived from the monoclonal antibody 14.G2a that has been approved for therapeutic use in children with neuroblastoma and has been used in previous clinical trials [33], an IgG1 (HCH 2 CH 3 ) hinge domain followed by the CD28 transmembrane (TM) domain, and the intracellular 4-1BB and CD3ζ signaling domains [25] ( Figure 1A). To verify the specificity and function of the G D2 CAR, the CAR was initially cloned into a third generation lentiviral self-inactivating (SIN) vector [34] under the control of the human phosphoglycerate kinase (hPGK) promoter (LV-G D2 CAR) and tested in a murine T cell hybridoma reporter cell line.…”
Section: Specificity and Function Of The G D2 Carmentioning
confidence: 99%
“…The amplified and sequenced fragment was cloned via three-fragment ligation into vector pRRL.PPT.PGK.newMCS.EBFP2.i2.Zeo.PRE using the XhoI and NheI sites between the cPPT and the hPGK promoter sequences. The human codon-usage optimized ORF second generation CAR containing scFv (14.G2a), HCH 2 CH 3 hinge, CD28, CD137 (4-1BB), and CD3ζ domains [25] was flanked by the restriction enzymes AgeI and SalI were cloned into the lentiviral "all-in-one" SIN vector driven by an hPGK promoter. The restriction sites MluI and EcoRI, or AfeI and EcoRI, respectively, were inserted to exchange the iGOI within the "all-in-one" vector construct (Figure 2A).…”
Section: Cloning Of "All-in-one" Vector Constructs Production and Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The successes of chimeric antigen receptor (CAR) T cell therapies targeting hematologic malignancies have not yet translated to solid tumors due to challenges with antigen selection, tumor trafficking, T cell persistence, and the tumor microenvironment (TME). In this issue of Molecular Therapy, Kailayangiri et al 1 report that inhibiting Enhancer of Zeste Homolog 2 (EZH2) to upregulate tumor antigen GD2 synthase (GD2) expression in Ewing sarcoma cells circumvents its variable expression. The combination of EZH2 inhibition therapy with CAR T cell therapies may therefore improve outcomes in Ewing sarcoma and potentially other malignancies.…”
mentioning
confidence: 99%